Is elective cancer surgery feasible during the lock‐down period of the COVID‐19 pandemic? Analysis of a single institutional experience of 404 consecutive patients. Issue 7 (23rd February 2021) - Kulle, Cemil Burak; Azamat, Ibrahim Fethi; Vatansever, Dogan; Erus, Suat; Tarim, Kayhan; Akyoldas, Goktug; Gokler, Ozan; Deveci, Mehmet Ali; Cakar, Nahit; Ergonul, Onder; Agcaoglu, Orhan; Kiremit, Murat Can; et al.
Abstract: Background: We aimed to assess the feasibility and short‐term clinical outcomes of surgical procedures for cancer at an institution using a coronavirus disease 2019 (COVID‐19)‐free surgical pathway during the peak phase of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic. Materials and Methods: This was a single‐center study, including cancer patients from all surgical departments, who underwent elective surgical procedures during the first peak phase between March 10 and June 30, 2020. The primary outcomes were the rate of postoperative SARS‐CoV‐2 infection and 30‐day pulmonary or non‐pulmonary related morbidity and mortality associated with SARS‐CoV‐2 disease. Results: Four hundred and four cancer patients fulfilling inclusion criteria were analyzed. The rate of patients who underwent open and minimally invasive procedures was 61.9% and 38.1%, respectively. Only one (0.2%) patient died during the study period due to postoperative SARS‐CoV2 infection because of acute respiratory distress syndrome. The overall non‐SARS‐CoV2 related 30‐day morbidity and mortality rates were 19.3% and 1.7%, respectively; whereas the overall SARS‐CoV2 related 30‐day morbidity and mortality rates were 0.2% and 0.2%, respectively. Conclusions: Under strict institutional policies and measures to establish a COVID‐19‐free surgical pathway, elective and emergency cancer operations can be performed with acceptable perioperative and postoperative morbidity and mortality.